2013
DOI: 10.1111/jfpp.12203
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Stability of Carotenoid-Containing Lipids from Hepatopancreas of Pacific White Shrimp (Litopenaeus vannamei )

Abstract: Impacts of extraction conditions on lipid and carotenoid yields from hepatopancreas of Pacific white shrimp (Litopenaeus vannamei) were investigated. Among single solvents (acetone, isopropanol and hexane) and their mixtures, a mixture of hexane and isopropanol (50:50, v/v) rendered lipids with the highest carotenoid yield (336.40 mg/kg hepatopancreas) with the extraction yield of 18.22% (w/w hepatopancreas) (P < 0.05). The use of hepatopancreas to solvent ratio of 1.0:4.5 (w/v) and three repetitions showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…For wet tissues, nonpolar solvents were inappropriate since their penetration through the hydrophobic mass surrounding the pigment is limited (Sachindra et al, ). Takeungwongtrakul Benjakul, Santoso, Trilaksani, and Nurilmala () extracted carotenoid from the hepatopancreas of Pacific white shrimp ( Litopenaeus vannamei ) by using acetone, isopropanol, and hexane and also by their mixtures. A 50:50 mixture of hexane and isopropanol had the highest carotenoid yield (336.40 µg g −1 hepatopancreas).…”
Section: Resultsmentioning
confidence: 99%
“…For wet tissues, nonpolar solvents were inappropriate since their penetration through the hydrophobic mass surrounding the pigment is limited (Sachindra et al, ). Takeungwongtrakul Benjakul, Santoso, Trilaksani, and Nurilmala () extracted carotenoid from the hepatopancreas of Pacific white shrimp ( Litopenaeus vannamei ) by using acetone, isopropanol, and hexane and also by their mixtures. A 50:50 mixture of hexane and isopropanol had the highest carotenoid yield (336.40 µg g −1 hepatopancreas).…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoid content of hepatopancreas of Pacific white LM S1 S2 S3 S4 S5 S6 S7 S8 S9 S10 S11 97 66 45 30 21 14.4 MW (kDa) Fig. 1 Protein patterns of various salted shrimp pastes, LM low-molecular weight marker, key: see Table 1 caption shrimp was 336.40 mg/kg sample (Takeungwongtrakul et al 2012a). Sachindra et al (2006) reported the highest carotenoid content (43.9 mg/kg sample) from head and carapace of Penaeus indicus when 50:50 (v/v) mixture of hexane and isopropanol was used as extracting medium.…”
Section: Carotenoid Contentmentioning
confidence: 99%
“…Oil was extracted from hepatopancreas following the method of Takeungwongtrakul et al (2014). The prepared hepatopancreas (20 g) was homogenized with 90 ml of cold solvent mixtures (isopropanol: hexane, 50: 50, v/v) (4°C) at the speed of 9500 rpm using an IKA Labortechnik homogenizer (Selangor, Malaysia) for 2 min at 4°C.…”
Section: Extraction Of Oils From Hepatopancreasmentioning
confidence: 99%